Empathy in Emotional Intelligence: An Analysis of Daniel Goleman’s Theory and the Qur’anic Perspective on the Aceh-Sumatra Flood Disaster 2025 - Husna, Ziyadatul; Huda , Nuril (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The 2025 Aceh-Sumatra flood disaster not only caused physical and material impacts but also gave rise to complex psychological and social issues. In this context, emotional intelligence and empathy become crucial factors in building individual resilience and social solidarity. This study aims to examine the concept of emotional intelligence according to Daniel Goleman, analyze empathy as the core of social awareness, and integrate it with the perspective of the Qur'an. This research uses a qualitative approach with a library research method. The primary data sources include the works of Daniel Goleman and the Qur'an, along with the Tafsir Fi Zhilal al-Qur'an by Sayyid Quthb, while secondary sources consist of relevant books and academic journals. Data analysis is conducted in a descriptive-analytical and integrative manner. The study findings show that Goleman's concept of emotional intelligence includes self-awareness, self-regulation, motivation, empathy, and social skills, which are interrelated. Empathy occupies a central position as a bridge between personal and social competencies. From the Qur'anic perspective, empathy is seen as a manifestation of faith reflected in brotherhood, social care, and gentleness of heart. The integration of Western theory and Islamic perspective demonstrates that empathy is not only a psychological skill but also a spiritual value that guides concrete actions in times of crisis. This research concludes that the integration of emotional intelligence and Qur'anic values can serve as the foundation for strengthening emotional and social education, as well as building a resilient and empathetic society in the face of disaster.